Growth and yield of rice (Oryza sativa) under different establishment methods and weed management practices in Uttarakhand - SINGH, D K; YADAV, SANTOSH K; KRISHNA, MAYA; RAWAT, SONAM; TRIPATHI, SUPRIYA; PUN, MEGHA; SINGH, P K; SHARMA, YOGESH (The Indian Journal of Agricultural Sciences, 2023)
An experiment was conducted during the rainy (kharif) seasons of 2021 and 2022 at the Norman E. Borlaug (NEB) Crop Research Centre at Govind Ballabh Pant University of Agriculture and Technology, Pantnagar, Uttarakhand to study the effect of different establishment methods and weed management practices on growth and yield of rice (Oryza sativa L.). The study was carried in a split plot design with 3 replications. In main plot 4 rice establishment methods and in sub plot 4 weed management practices were included. The results revealed that significantly higher grain yield was recorded in mechanical line sowing (S2) over rest of the treatment. According to the pooled data analysis of grain yield the per cent increase in mechanical line sowing (S2) over broadcasting (S1), raised bed system (S3) and semi-dry system (S4) was 23.1%, 17.6% and 8.1%, respectively. Among the different weed management practices grain yield was recorded maximum in W3 (pre emergence herbicide followed by two manual weeding) treatment which showed at par results with W2 (pre emergence followed by post emergence herbicide) treatment. The per cent grain yield increase in pre emergence herbicide followed by two manual weeding (W3) over manual weeding (W1), pre emergence followed by post emergence herbicide (W2) and mechanical weeding (W4) was 19.3%, 0.75% and 31.7%, respectively. Weed density was recorded minimum in mechanical line sowing (S2) and raised bed system (S3). At panicle initiation stage significantly lower weed density was recorded in mechanical line sowing (S2). However, among the weed management practices manual weeding (W1) and pre emergence herbicide followed by two manual weeding (W3) treatments recorded at par. Weed dry weight remain non-significant under different rice establishment methods during active tillering as well as panicle initiation stage.